Domestic Intelligence: Leonora and National Security. Issue 1 (2nd January 2021) - Weiss, Deborah
ABSTRACT: Maria Edgeworth's epistolary novel Leonora, published in 1806, was one of her most unpopular works. To this day, it is the most under-examined novel she wrote during her period of peak popularity. Leonora tells a story of adultery that brings the dangers posed by Napoleonic France into the English domestic realm. Lady Olivia, returning to England from France, is invited by Lady Leonora to stay at L Castle, where she soon embarks on an affair with her friend's husband. Edgeworth models this adulterous plot on Germaine de Staël's Delphine, and she blends her mimicry of de Staël's novel with an extensive critique of Mary Wollstonecraft's The Wrongs of Woman; or, Maria . The target of Edgeworth's mockery and criticism is radical sensibility, particularly its moralization of individual feeling and support for adultery and divorce. Edgeworth uses Leonora not just to support marriage and domestic attachment, but also to wrest female intellectuality back from Wollstonecraft's tarnished reputation. Through writing a novel that debates with de Staël and Wollstonecraft, Edgeworth reclaims the female intellectual as a figure who promotes social stability; and she shows how morally strong, rational women operating from within the domestic realm can contribute to national security.